Prognostic factors in oral cancer surgery - results from a UK tertiary centre. Issue 4 (April 2023) - Kanatas, Anastasios; Walshaw, Emma G.; Wu, Jianhua; Fabbroni, Gillon; Chengot, Preetha
Abstract: Introduction: Oral cancer surgery is complicated by the diverse nature of clinical and histopathological presentations that occur. Current National guidance recognises the significant role that surgical margin status plays in the overall survival of patients. Many other histopathological factors influence patient survival, the importance of which varies between the literature. Materials and methods: In this prospective longitudinal study, all patients diagnosed with squamous cell carcinoma who had primary surgical treatment under general anaesthesia were included. Surgery was performed by one surgical team within this tertiary referral centre. Patients were followed up for a maximum of 7 years following their surgery. Results: A total of 250 patients were included from 2015 to 2022. Patients were 61.44 years old (SD 13.23) at diagnosis, and 56.4% were male (n = 141). Pathology was mainly pT1 (39.1%) and the most common sites were the border of tongue (31.2%) and floor of mouth (18.8%). 43.4% of patients had clear surgical margins, with overall survival being significantly associated with margin status (p = 0.0079). Extra-capsular spread was significantly associated with higher risk of death from metastatic head and neck cancer (p = 0.014), whereas presence of high-grade dysplasia at surgical margins and depth of invasion of tumour were not. Conclusion: This study has reinforced the importance of surgical margin clearance and as such the development of intra-operative techniques to ensure this is imperative. The significance of extra-capsular spread in survival has also been demonstrated. Discussion regarding the current deficiency in accurate pre-operative diagnostic methods for extra capsular spread is covered.